(untitled) (European Journal of Marketing and Economics, 2018)
Foreign direct investment is believed to enhance long-term economic growth of a country through knowledge spillovers and technology transfers. This paper is an empirical attempt to check the effects of the foreign direct investment (FDI) on the economic growth (GDP) of Turkey. The paper uses time span from 1980 to 2017 for statistical analysis. Johansen co-integration and Granger causality tests were applied for empirical analysis. The results of the tests confirmed the presence of the co-integration between GDP and FDI as it was expected from the beginning. Furthermore, Granger causality test showed the unidirectional causality from FDI to GDP.